Lipid bilayer-atomic force microscopy combined platform records simultaneous electrical and topological changes of the TRP channel Polycystin-2 (TRPP2) - Lal S (2018)
Ion channels are transmembrane proteins that mediate ion transport across biological membranes. Ion channel function is traditionally characterized by electrical parameters acquired with techniques such as patch-clamping and reconstitution in lipid bilayer membranes (BLM) that provide relevant information such as ionic conductance, selectivity, and gating properties. High resolution structural information of ion channels however, requires independent technologies, of which atomic force microscopy (AFM) is the only one that provides topological features of single functional channel proteins in their native environments. To date practically no data exist on direct correlations between electrical features and topological parameters from functional single channel complexes. Here, we report the design and construction of a BLM reconstitution microchamber that supports the simultaneous recording of electrical currents and AFM imaging from single channel complexes. As proof-of-principle, we tested the technique on polycystin-2 (PC2, TRPP2), a TRP channel family member from which we had previously elucidated its tetrameric topology by AFM imaging, and single channel currents by the BLM technique. The experimental setup provided direct structural-functional correlates from PC2 single channel complexes that disclosed novel topological changes between the closed and open sub-conductance states of the functional channel, namely, an inverse correlation between conductance and height of the channel. Unexpectedly, we also disclosed intrinsic PC2 mechanosensitivity in response to external forces. The platform provides a suitable means of accessing topological information to correlate with ion channel electrical parameters essential to understand the physiology of these transmembrane proteins.